High-Performance Liquid Crystalline Polymer for Intrinsic Fire-Resistant and Flexible Triboelectric Nanogenerators - Guan, Qingbao (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.